PENGEMBANGAN INSTRUMEN EVALUASI SOAL PILIHAN GANDA BERBASIS HOT POTATOES PADA MATA KULIAH STATISTIK - Iesyah Rodliyah; Sari Saraswati (Prodi Pendidikan Matematika FKIP Universitas Madura, 2020)
This study aims to describe each stage of the development of a statistical learning outcome evaluation test instrument which is packaged using an IT-based learning evaluation media application, namely Hot Potatoes. The development model used in this study is the ADDIE model which consists of five stages, namely (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The subjects of the trials in this development research included material experts, media experts, and mathematics education students who taught statistics courses. The research data were collected through tests and questionnaires. The research data were analyzed using descriptive analysis techniques. The resulting research product was a test instrument in the form of multiple choice questions using Hot Potatoes based learning evaluation media. The results of the analysis showed that the product in the form of a hot potato-based statistical test question instrument was declared feasible to be used in evaluating student learning outcomes and met the criteria of being valid, practical, and effective